Caracterización de los Sistemas de Producción Pecuaria Asociativa Comunitaria en la Provincia de Cotopaxi. - Miranda Quillupangui, Cristian Iván (2019)
This research was carried out in order to evaluate the number of community livestock associations which exist in the province of Cotopaxi, in the rural parishes of: Zumbahua, Guangaje, La Matriz, Pilaló, Poalo, Aláquez, Toacazo, Pastocalle, Tanicuchí, Saquisilí, Pujilí; Themain objectiveis to evaluatethe conditions and the different activities that are developed in each of the producers owners associations and in the same associations. For the development of the research, individual field surveys were carried out to each of the producers through an established schedule and prior contact with each one, in order to apply the questionnaire in their farm, in this research the asked questions evaluate: general data of the respondent, social information about being part of a community organization; What type of institutions is your project intervened for?; productive information; categorization of animals; driving; health and feeding in the three species investigated (cattle, sheep and guinea pigs). As a result, It was noticed that all the producers and associations surveyed, belong to a community organization, and that the majority of them are intervened by governmental entities, which provide technical training to the interested parties, in addition It is mention that the majority of respondents have a clear idea of the objective production and know the processes of handling nutrition, reproduction and health that their animals need.